Every Breath You Take : Under Suspicion #5 - Clark, Mary Higgins; Burke, Alafair (New York : Simon & Schuster, 2017)
Forced to team up with Ryan Nichols, television crime solver Laurie Moran investigates a new cold case involving the death of a wealthy woman who was pushed off the roof of the Metropolitan Museum of Art.
Keywords: Television programs -- Fiction; Television personalities -- Fiction; Murder -- Investigation -- Fiction; Cold cases (Criminal investigation) -- Fiction; Television programs -- Fiction; Television personalities -- Fiction; Homicide -- Fiction; Criminal investigation -- Fiction; Suspense fiction